PERSIAN CUED SPEECH: THE EFFECT ON PHONOLOGICAL COMBINATION AND SEGMENTATION SKILLS OF CHILDREN WITH INTELLECTUAL DISABILITY - Movallali, G.; Shakouri, M.; Taheri, M.; Arefi, M.; Salehy, Z. (European Scientific Journal, ESJ, 2015)
The aim of this paper was to study the effect of a Persian Cued Speech training program for increasing the phonological combination and segmentation skills of intellectually disabled children. This study was a quasi–experimental study. A convenience sample was selected and divided in two groups, namely an experimental group and a control group (n = 5). The study used the Phonological Awareness Questionnaire as the tool of analysis. The Cued Speech training is a forty 90-minute session program, which was implemented on the experimental group. At the end of the program, they were again assessed with the questionnaire. The findings from the study show the efficacy of our intervention on increasing the Phonological Combination and Segmentation skills (P < 0/10, P < 0/05). Using Cued Speech with the intellectually disabled children can be helpful to develop their pre reading skills such as phonological awareness.